2011
DOI: 10.1213/ane.0b013e3182185fee
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Dual Effects of Anesthetic Isoflurane on Hypoxia-Induced Caspase-3 Activation and Increases in β-Site Amyloid Precursor Protein-Cleaving Enzyme Levels

Abstract: Background β-amyloid protein (Aβ) accumulation, caspase activation, apoptosis, and hypoxia-induced neurotoxicity have been suggested to be involved in Alzheimer disease neuropathogenesis. Aβ is produced from amyloid precursor protein (APP) through proteolytic processing by the aspartyl protease β-site APP-cleaving enzyme (BACE) and γ-secretase. Inhaled anesthetics have long been considered to protect against neurotoxicity. However, recent studies have suggested that the inhaled anesthetic isoflurane may promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…It is important and urgent to have well-designed clinical studies for confirmation of possible neurotoxic effects of general anesthetics in human developing brains. On the other hands, the patients almost always receive surgeries when they received general anesthesia, while these surgical stimulation may have significant effects on neuronal apoptosis in the developing brain induced by general anesthetics 65;66 …”
Section: Role Of Ca2+ In Anesthetics-induced Neurotoxicitymentioning
confidence: 99%
“…It is important and urgent to have well-designed clinical studies for confirmation of possible neurotoxic effects of general anesthetics in human developing brains. On the other hands, the patients almost always receive surgeries when they received general anesthesia, while these surgical stimulation may have significant effects on neuronal apoptosis in the developing brain induced by general anesthetics 65;66 …”
Section: Role Of Ca2+ In Anesthetics-induced Neurotoxicitymentioning
confidence: 99%
“…Recently, investigations showed dual effects (protection versus promotion) of isoflurane on Aβ-induced apoptosis, which may act through Bcl-2 family proteins [22,23]. Liu et al [24] reported that isoflurane induced spatial memory impairment through a mechanism independent of Aβ levels and tau protein, but the rats in their investigation just received 1.4% isoflurane for 2 hr.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigations showed that anesthetic-induced neural damage has similar mechanisms with Alzheimer's disease (AD) [5,6]. AD presents memory loss followed by a progressive dementia and is characterized by extensive atrophy of the brain caused by series neurodegeneration, including generation of β-amyloid (Aβ), appearance of neurofibrillary tangles, and neuronal and synaptic loss [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Isoflurane has been shown to cause dose-and duration-dependent dual effects on caspase 3 activation (protection or potentiation). 38,39 Thus, it is possible that isoflurane may induce similar dual effects on mitochondrial function (eg, mPTP opening), learning, and memory. Future studies may include a systematic investigation of the effects of isoflurane and other anesthetics (eg, desflurane, sevoflurane, and propofol) on opening of mPTP, levels of MMP, ATP, and ROS, and learning and memory function to further test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%